ALMA survey of Lupus class III stars: Early planetesimal belt formation and rapid disc dispersal. Issue 4 (28th October 2020) - Lovell, J B; Wyatt, M C; Ansdell, M; Kama, M; Kennedy, G M; Manara, C F; Marino, S; Matrà, L; Rosotti, G; Tazzari, M; Testi, L; Williams, J P
ABSTRACT: Class III stars are those in star forming regions without large non-photospheric infrared emission, suggesting recent dispersal of their protoplanetary discs. We observed 30 class III stars in the 1–3 Myr Lupus region with ALMA at ∼856μm, resulting in four detections that we attribute to circumstellar dust. Inferred dust masses are 0.036–0.093 M ⊕, ∼1 order of magnitude lower than any previous measurements; one disc is resolved with radius ∼80 au. Two class II sources in the field of view were also detected, and 11 other sources, consistent with sub-mm galaxy number counts. Stacking non-detections yields a marginal detection with mean dust mass ∼0.0048 M ⊕ . We searched for gas emission from the CO J = 3–2 line, and present its detection to NO Lup inferring a gas mass (4.9 ± 1.1) × 10 −5 M ⊕ and gas-to-dust ratio 1.0 ± 0.4. Combining our survey with class II sources shows a gap in the disc mass distribution from 0.09–2 M ⊕ for 0.7 M_ Lupus stars, evidence of rapid dispersal of mm-sized dust from protoplanetary discs. The class III disc mass distribution is consistent with a population model of planetesimal belts that go on to replenish the debris discs seen around main sequence stars. This suggests that planetesimal belt formation does not require long-lived protoplanetary discs, i.e. planetesimals form within ∼2 Myr. While all four class III discs are consistent with collisional replenishment, for two the gas and/or mid-IR emission could indicate primordial circumstellar material in the final stages of protoplanetary disc dispersal. Two class III stars without sub-mm detections exhibit hot emission that could arise from ongoing planet formation processes inside ∼1 au.